Aortic valve-sparing root replacement (David): learning curve and impact on outcome. (23rd January 2020) - Beckmann, Erik; Martens, Andreas; Krueger, Heike; Kaufeld, Tim; Korte, Wilhelm; Stettinger, Alissa; Haverich, Axel; Shrestha, Malakh Lal
Abstract: OBJECTIVES: Aortic valve-sparing root replacement (David procedure) offers the benefit of preserving the native aortic valve but is often criticized for being technically challenging and time-consuming. We analysed whether the surgeon's level of experience affects the early and long-term outcome after the David procedure. METHODS: From July 1993 to October 2015, a total of 582 patients underwent aortic valve-sparing David I procedure at our institution. A retrospective review with follow-up (mean follow-up time 8.6 ± 5.6 years) was performed. Statistical analysis of the surgeon's level of experience was performed as a categorical variable, after patients were chronologically assigned to groups of tens. Study end points assessing the surgeon's learning curve included both measures of patient outcome and measures of task efficiency. Study end points included both short- and long-term outcomes. RESULTS: Analysis of task efficiency showed that there was a statistically significant inverse correlation between the surgeon's level of experience and both cardiopulmonary bypass time ( P = 0.026) and aortic cross-clamp time ( P = 0.017). Analysis of patient outcome revealed that the incidence of aortic valve-related reoperation during follow-up showed a significant inverse correlation with the surgeon's level of experience ( P = 0.048). Cox regression analysis found that the surgeon's level of experience (odds ratio 0.802, 95% confidence interval 0.673–0.957; P = 0.014) was a significant risk factor for aortic valve-related reoperation-free survival during follow-up. CONCLUSIONS: There is a surgeon's learning curve for aortic valve-sparing David procedure. The surgeon's experience has a direct impact on both the perioperative outcome and the long-term performance of the aortic valve.